All‐Inorganic Perovskite‐Based Monolithic Perovskite/Organic Tandem Solar Cells with 23.21% Efficiency by Dual‐Interface Engineering. Issue 16 (15th February 2023) - Sun, Shuang‐Qiao; Xu, Xiuwen; Sun, Qi; Yao, Qin; Cai, Yating; Li, Xin‐Yi; Xu, Yan‐Lin; He, Wei; Zhu, Min; Lv, Xuan; Lin, Francis R.; Jen, Alex K.‐Y.; et al.
Abstract: Monolithic perovskite/organic tandem solar cells (POTSCs) have significant advantages in next‐generation flexible photovoltaics, owing to their capability to overcome the Shockley–Queisser limit and facile device integration. However, the compromised sub‐cells performance challenges the fabrication of high‐efficiency POTSCs. Especially for all‐inorganic wide‐bandgap perovskite front sub‐cells (AIWPSCs) based n‐i‐p structured POTSCs (AIPOTSCs), for which the power conversion efficiency (PCE) is much lower than organic–inorganic mixed‐halide wide‐bandgap perovskite based POTSCs. Herein, an ionic liquid, methylammonium formate (MAFm), based dual‐interface engineering approach is developed to modify the bottom and top interfaces of wide‐bandgap CsPbI2 Br films. In particular, the Fm − group of MAFm can effectively passivate the interface defects, and the top interface modification can facilitate the formation of uniform perovskite films with enlarged grain size, thereby mitigating the defects and perovskite grain boundaries induced carrier recombination. As a result, CsPbI2 Br‐based AIWPSCs with a high PCE of 17.0% and open‐circuit voltage ( V OC ) of 1.347 V are achieved. By integrating these dual‐interface engineered CsPbI2 Br‐based front sub‐cells with the narrow‐bandgap PM6:CH1007‐based rear sub‐cells, a record PCE of 23.21% is obtained for AIPOTSCs, illustrating the potential of AIPOTSCs for achieving high‐efficiency tandem solar cells. Abstract : The ionic liquid, methylammonium formate (MAFm), based dual‐interface engineering is developed to modify the bottom and top interfaces of wide‐bandgap CsPbI2 Br films, which enables a high PCE of 17.0% and V OC of 1.347 V for CsPbI2 Br‐based wide‐bandgap sub‐cells. High‐efficiency monolithic perovskite/organic tandem solar cells based on these sub‐cells demonstrate a champion PCE of 23.21% and V OC of 2.10 V.